Thermokarst Lagoons: A Core-Based Assessment of Depositional Characteristics and an Estimate of Carbon Pools on the Bykovsky Peninsula - Jenrich, Maren; Angelopoulos, Michael; Grosse, Guido; Overduin, Pier Paul; Schirrmeister, Lutz; Nitze, Ingmar; Biskaborn, Boris K.; Liebner, Susanne; Grigoriev, Mikhail; Murray, Andrew; Jongejans, Loeka L.; Strauss, Jens (Frontiers in Earth Science, 2021)
Permafrost region subsurface organic carbon (OC) pools are a major component of the terrestrial carbon cycle and vulnerable to a warming climate. Thermokarst lagoons are an important transition stage with complex depositional histories during which permafrost and lacustrine carbon pools are transformed along eroding Arctic coasts. The effects of temperature and salinity changes during thermokarst lake to lagoon transitions on thaw history and lagoon deposits are understudied. We analyzed two 30-m-long sediment cores from two thermokarst lagoons on the Bykovsky Peninsula, Northeast Siberia, using sedimentological, geochronological, hydrochemical, and biogeochemical techniques. Using remote sensing we distinguished between a semi-closed and a nearly-closed lagoon. We (1) characterized the depositional history, (2) studied the impact of marine inundation on ice-bearing permafrost and taliks, and (3) quantified the OC pools for different stages of thermokarst lagoons. Fluvial and former Yedoma deposits were found at depth between 30 m and 8.5 m, while lake and lagoon deposits formed the upper layers. The electrical conductivity of the pore water indicated hypersaline conditions for the semi-closed lagoon (max: 108mS/cm), while fresh to brackish conditions were observed beneath a 5m-thick surface saline layer at the nearly-closed lagoon. The deposits had a mean OC content of 15±2kg/m³, with higher values in the semi-closed lagoon. Based on the cores we estimated a total OC pool of 5.7 Mt-C for the first 30m of sediment below five mapped lagoons on the Bykovsky Peninsula. Our results suggest that paleo river branches shaped the middle Pleistocene landscape followed by late Pleistocene Yedoma permafrost accumulation and early Holocene lake development. Afterwards, lake drainage, marine flooding, and bedfast ice formation caused the saline enrichment of pore water, which led to cryotic talik development. We find that the OC-pool of Arctic lagoons may comprise a substantial inventory of partially thawed and partially refrozen OC, which is available for microbial degradation processes at the Arctic terrestrial-marine interface. Climate change in the Arctic leading to sea level rise, permafrost thaw, coastal erosion, and sea ice loss may increase the rate of thermokarst lagoon formation and thus increase the importance of lagoons as biogeochemical processors of former permafrost OC.